Negotiating Marital Communication in the Digital Era: Social Media Use among Working Couples from a Family Law Perspective - Muhammad Yanis; Bukhari Ali; Yenny Sri Wahyuni; Nurul Ain Hazram; Hisyam Maliki Akbar (An-Nisa: Journal of Islamic Family Law, 2025)
This study aims to identify and analyze the communication patterns of married couples who work in using social media effectively and adaptively to maintain household harmony. This study uses a qualitative descriptive method with the determination of informants based on the principle of data saturation, considering that the population number is not known for sure. A total of 12 informants who were married couples with formal employment status were randomly selected. Data collection was carried out through in-depth interviews and thematic analysis. The results of the study show that face-to-face communication remains the most crucial and effective foundation in maintaining household harmony, especially in resolving sensitive issues and deep conflicts. Meanwhile, social media functions as a complement to practical communication, especially in conditions of limited time, long distance relationships, and as a means of defusing conflicts in the early stages. However, the majority of informants consider that social media is not yet fully effective in conveying crucial issues such as criticism and differences of opinion due to the high risk of misunderstandings. These findings indicate that household harmony (sakinah, mawaddah, and rahmah) is supported by the application of interpersonal communication norms, such as openness, emotional control, mutual respect, and the establishment of ethical boundaries in digital behavior to prevent conflicts, including the potential for online infidelity. Based on these findings, this study recommends that married couples who actively work build a balanced communication agreement between face-to-face communication and social media utilization, accompanied by digital communication literacy oriented towards ethical values and family resilience.